Comparison of Levothyroxine Dosing in Patients with and without Heart Failure. (2nd January 2020) - Yang, Tianrui; Ruegger, Melanie; Colavecchia, A. Carmine; Sadhu, Archana; Patham, Bhargavi; Tatara, Alexandra
ABSTRACT: Background : Evidence has shown that low thyroid hormone levels may lead to worse prognosis including a higher mortality rate in patients with heart failure (HF). Thyroid replacement increases cardiac output and exercise performance without causing significant adverse events. The purpose of this study is to compare levothyroxine doses in patients with and without HF. Methods : This single center, retrospective cohort study compared levothyroxine doses in ambulatory hypothyroid patients with a history of HF to those without a history of HF. Patients were stratified into three groups: no HF, HF with reduced ejection fraction (HFrEF, EF<40%), and other types of HF. The primary endpoint of average levothyroxine dose was analyzed using multivariable linear regression with variables determined a priori . Results : Three hundred patients were included in the study with 100 patients in each arm. Average levothyroxine doses (mcg/kg) were 1.5 ± 0.7, 1.6 ± 0.8, and 1.6 ± 0.9 for no HF, other types of HF, HFrEF, respectively ( p = .61). Factors found to be significantly related to levothyroxine dosing included gender, drug–drug interactions, and the timing of clinic visit to lab draw. No differences were found in secondary outcomes including TSH levels, free T4, T3, and percentage of patients with elevated thyroid-stimulating hormone (TSH) among HFrEF, other types of HF, and no HF patients. Among HF patients, average ejection fractions were also similar comparing patients with elevated TSH, normal TSH, and low TSH. Conclusion : The dose of levothyroxine was not significantly different in HF patients compared to patients without HF.